ANALISIS PENGENDALIAN KUALITAS UNTUK MENGURANGI DEFECTS PRODUCTS PADA PACKAGING LINE DENGAN MENGGUNAKAN METODE QUALITY CONTROL CIRCLE PADA PT XYZ - Noorulloh Fajrezi (2022)
This research discusses the analysis of quality control to be able to reduce defects products on the packaging line PT XYZ by using the Quality Control Circle method. As a palm oil company in Indonesia, quality control is essential for PT XYZ. In this study, the researcher uses the Quality Control Circle method as a recommendation for the improvement of PT XYZ quality control. To sum up the research, Unprecise Cardboard has the most dominant defect came with a value of 17381 pcs with highest defect percentage as much as 2.60%. In addition, the results of the fishbone diagram show that there are several causes of defects on the unprecise cardboard, particularly from machine, materials, and methods used. From the results of this research, PT XYZ can reduce defects products on the packaging line by periodically checking the methods and materials used also ensuring the condition of the machines used in normal conditions constantly.